The Labour Market Returns to Sleep - Joan Costa-Font; Sarah Fleche; Ricardo Pagan; Joan Costa-i-Font (Center for Economic Studies and ifo Institute (CESifo), 2022)
The proportion of people sleeping less than the daily-recommended hours has increased. Yet, we know little about the labour market returns to sleep. We use longitudinal data from Germany and exploit exogenous variation in sleep duration induced by time and local variations in sunset time. We find that a 1-hour increase in weekly sleep increases employment by 1.6 percentage points and weekly earnings by 3.4%. Most of this earnings effect comes from productivity improvements, while the number of working hours decreases with sleep time. We identify one mechanism driving these effects, namely the better mental health workers experience from sleeping more hours.
Keywords: I18; J12; J13; 330; sleep; employment; productivity; mental health; sunset times